Pakriti O narir ekadata : Prasanga Tilottama Majumdarer ‘Rajpath’ Uponyas/ প্রকৃতি ও নারীর একাত্মতা : প্রসঙ্গ তিলোত্তমা মজুমদারের ‘রাজপাট’ উপন্যাস (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
The title of this research work is – ‘‘Tilottama Majumdar's Novel 'Rajpat' on the Unity of Nature and Women.’’ Tilottama Majumdar can be called a brilliant astrologer in the sky of Bengali fiction. He entered the world of literature by writing stories in 'Unmesh' magazine. In this research work, I have tried to show that in the novel 'Rajpat' he has highlighted the issues of ecofeminism in some contexts. From the beginning of creation of nature, women have experienced nature very closely. I have tried to highlight how the patriarchal society maintains control over women by feminizing nature and naturalizing women. Environmental feminists think that if we look at women and nature from a historical point of view, we will see that the oppression of women and the oppression of nature are tied together. Environmental feminism is a philosophical approach, emphasizing women's rights and protecting the environment, even calling for women to calm nature, protect nature. These various aspects have been specifically tried to be highlighted in this research work.
Keywords: Environmental feminism; unity of nature and women; conservation of environment; torture and oppression of nature and women; demand for fair rights of women